(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
Through qualified FDA approved workflows and regulations 3d printed patient specific implants like cranial plates printed from PEEK becomes reality. But besides implants also trials sizes, spacer, surgery tools or other short-term devices follows these success stories more and more often. Printed from commonly used materials in the medical industry like PPSU, PEEK and carbon fiber enhanced PEEK a brought range or application field could be covered by filament based additive manufacturing. Through DIN EN ISO 10993 approved materials in combination with the qualified Kumovis R1 printing technique medical devices for the whole orthopedic market is already possible. From joint reconstruction over spine until trauma market applications, way beyond orthosis or cutting guides, can be experienced a disruptive change. Using 3d printing to manufacture short-term devices from high performance polymers enable a huge range of benefits in terms of material as well as overall cost effectiveness. By substituting current metal-based devices to plastics like PPSU leads to a huge reduction in weight per part and therefore for whole trays of trials and instruments. Using additives like barium sulphate for x-ray visibility a complete substitution without losses in terms of performance or medical needs can be ensured. But even more important, next to natural given material benefits, are the enormous cost efficiency that could be reached throughout FFF printing also against machining or injection molding especially for small series or special sizes. Additive manufacturing even opens further advantages and develop their full potential if devices special designed for 3d printing to add functions and structures that are only possible by using an additive instead of subtractive manufacturing techniques. Bottom line multiple use short-term devices and tools applicable up to 500 sterilization cycles with 3d printing becomes more and more efficient in functionality and production costs.